2014
DOI: 10.5433/1679-0359.2014v35n2p1071
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos de dietas contendo concentrados proteicos vegetais no desempenho e atividade de enzimas digestivas de jundiá (Rhamdia quelen)

Abstract: ResumoO objetivo do estudo foi avaliar o efeito da utilização de concentrados proteicos de farelos de girassol e crambe na dieta de juvenis de jundiá, como substitutos da fonte proteica de origem animal. Foram utilizados 300 jundiás criados em 15 unidades experimentais de 280 L, constituindo cinco tratamentos com três repetições. Foram avaliados dois níveis (25 e 50%) de substituição da proteína da farinha de carne e ossos suína pelos concentrados proteicos de farelos de girassol e crambe. Avaliaramse parâmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
0
8
1
4
Order By: Relevance
“…These results are in agreement with those found by Hansen, Rosenlund, Karlsen, Koppe, and Hemre (), Cheng et al () and Ye, Liu, Wang, and Wang () in which the proximate chemical composition did not exhibit any change with different levels of inclusion of plant protein in the diet. However, these results do not corroborate those found by Gaber () and Lovatto et al () in which the levels of inclusion of protein concentrates affected the body composition.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…These results are in agreement with those found by Hansen, Rosenlund, Karlsen, Koppe, and Hemre (), Cheng et al () and Ye, Liu, Wang, and Wang () in which the proximate chemical composition did not exhibit any change with different levels of inclusion of plant protein in the diet. However, these results do not corroborate those found by Gaber () and Lovatto et al () in which the levels of inclusion of protein concentrates affected the body composition.…”
Section: Discussioncontrasting
confidence: 96%
“…The lowest FC observed in the fish that were fed the RBPC10 and RBPC15 diets can be explained by the smaller thickness of the fillet (Bonaldo et al, ). Lovatto et al () also found a lower FC in jundiás fed diets containing 250 and 500 g/kg crambe protein concentrate as a substitute for animal protein, which was attributed to the nutritional adaptation of fish to the experimental diets.…”
Section: Discussionmentioning
confidence: 93%
“…A utilização de farelo de crambe na alimentação animal vem sendo estudada principalmente para ruminantes como bovinos de corte (Mendonça et al, 2015), bovinos de leite (Oliveira et al, 2016) e ovinos (Goes et al, 2010;Dorigon e Gai (2016), entretanto, são escassos os estudos para os não ruminantes, havendo alguns trabalhos com juvenis de jundiá (Lovatto et al, 2014;Pettro et al, 2014), tilápias do Nilo (Moura et al, 2015) e frangos de corte (Ledoux et al, 1999). Portanto, objetivou-se com o presente trabalho determinar o desempenho de frangos de corte na fase inicial de vida, alimentados com farelo de crambe como fonte proteica para a ração.…”
Section: Resultsunclassified
“…meal (Robinson & Li 1994), sunflower meal protein concentrate and crambe meal protein concentrate (Lovatto et al 2014), linseed meal (Goulart et al 2013(Goulart et al , 2015. However, pumpkin kernel press has been investigated in other species, such as Arctic charr (Murray et al 2014), and it is currently being examined as a potential ingredient for fish feed.…”
Section: Aquaculture Nutritionmentioning
confidence: 99%
“…), cottonseed meal (Robinson & Li ), sunflower meal protein concentrate and crambe meal protein concentrate (Lovatto et al . ), linseed meal (Goulart et al . , ).…”
Section: Introductionmentioning
confidence: 99%